Darrieus-type vertical axis rotary-wings with a new design approach grounded in double-multiple streamtube performance prediction model - Batista, Nelson (2019)
Exploitation of wind energy with vertical axis rotary-wing has advantage over horizontal axis rotary-wing in areas where the wind is turbulent and unstable, i.e., with fast changes either in direction or velocity as normal happens in urban areas. The Darrieus-type vertical axis rotary-wing is experiencing a growth in interest for development and installation due to a growing interest in decentralizing energy conversion. This growth is expected to be in further augment in what concerns the way of the future, i.e., the smart grid environment. A problem linked with this Darrieus-type rotary-wing is the complexity in the performance prediction study, since the blades move around the rotor in 360°. An approach to the double-multiple streamtube performance prediction model for the vertical axis rotary-wing is offered in this paper, offering a flexible adapted tool when the airfoils lift and drag data are not available, or when more complex blade profiles of rotary-wings are in development. A new Darrieus-type vertical axis rotary-wing design is carried out with the approach offered, allowing for a self-start capable blade profile, having an adequate performance at high tip speed ratios. Several field tests are offered providing validation to the self-start, low noise and stable performance of the new rotary-wing design. Also, a modeling, control and simulation of grid integration are presented.